Decomposing the functional relationship between speed of information processing in the Hick paradigm and mental ability: A fixed-links modeling approach. (1st November 2017) - Rammsayer, Thomas H.; Pahud, Olivier; Troche, Stefan J.
Abstract: In his scholarly work, Bob Stelmack insistently reminded that response times represent an index of various cognitive processes that are unlikely to be functionally related to individual differences in mental ability to the same extent. Here, we introduce a fixed-links modeling approach to cope with this so-called impurity problem inherent in virtually all reaction time (RT) measures used within the mental speed approach to intelligence. For this purpose, we decomposed the variance of individual differences in RT obtained with the Hick RT paradigm into an experimental latent variable (LV) representing individual differences in RT associated with the systematically increased number of response alternatives in the Hick task, and a non-experimental LV representing individual differences in RT unrelated to this experimental manipulation. While the experimental LV explained a significant portion of 11.6% of variance in mental ability, the non-experimental LV accounted for only 2.6%. This outcome clearly indicates that, with the Hick RT paradigm, the functional relationship between speed of information processing and mental ability is primarily caused by individual differences in decision latency as a function of the experimentally increased number of response alternatives. Fixed-links modeling proved to be a highly suitable procedure to deal with the impurity problem. Highlight: RT variance caused by increasing number of binary decisions predicts mental ability. RT variance due to residual latency is unrelated to mental ability. Fixed-links modeling proved to be highly suitable to cope with the impurity problem.